Determination of the Effectiveness of Oral Midazolam as a Pre-medication in Paediatric Patients: A Brief Overview - Jayashree Phaltankar; Milin Shah (Research Developments in Medicine and Medical Science Vol. 1, 2023)
This chapter aims to assess the efficacy and safety of oral midazolam to reduce the anxiety and improve behaviour in children undergoing general anaesthesia. The aim of premedication in the paediatric age group is to produce sedation and anxiolysis, reduce emotional trauma and facilitate parental separation besides quiet and smooth induction of anaesthesia. In a double-blind randomised clinical trial, 90 children aged 1 to 8 years were randomly assigned to one of three oral premedication groups. Each group had 30 children. Group I received 0.5 mg/kg oral midazolam, while Group II received 0.75 mg/kg oral midazolam in a total volume of 5 ml of 25% dextrose. A 5 ml dose of 25% dextrose was given to Group III or the control group. We investigated the onset and depth of sedation, changes in vital signs like heart rate, blood pressure, and mental state before and after sedation, as well as any side effects that might have occurred after the procedure. After premedication, The difference in pulse rate, systolic blood pressure and respiratory rate between the three groups were not statistically significant Sedation at 30 minutes after premedication was better in study group II as compared to study group I The emotional state was concluded to be better in study Group II (0.75 mg/ kg) as compared to study group I (0.5 mg/kg) at the time of separation from parents. More post-operative complications like nausea, vomiting, giddiness, and headache were seen with a dose of 0.75 mg/kg than with a dose of 0.5 mg/kg. It is concluded that premedication with oral midazolam at a dose of 0.5 mg/kg in paediatric patients results in good to outstanding sedation within 30 minutes of separation from parents, with greater quality of separation. Additionally, it offers a steady emotional state throughout induction, with less postoperative problems and little hemodynamic alterations.